Interplay of brain structure and function in neonatal congenital heart disease. Issue 9 (14th August 2016) - Birca, Ala; Vakorin, Vasily A.; Porayette, Prashob; Madathil, Sujana; Chau, Vann; Seed, Mike; Doesburg, Sam M.; Blaser, Susan; Nita, Dragos A.; Sharma, Rohit; Duerden, Emma G.; Hickey, Edward J.; et al.
Abstract: Objective: To evaluate whether structural and microstructural brain abnormalities in neonates with congenital heart disease (CHD) correlate with neuronal network dysfunction measured by analysis of EEG connectivity. Methods: We studied a prospective cohort of 20 neonates with CHD who underwent continuous EEG monitoring before surgery to assess functional brain maturation and network connectivity, structural magnetic resonance imaging (MRI) to determine the presence of brain injury and structural brain development, and diffusion tensor MRI to assess brain microstructural development. Results: Neonates with MRI brain injury and delayed structural and microstructural brain development demonstrated significantly stronger high‐frequency (beta and gamma frequency band) connectivity. Furthermore, neonates with delayed microstructural brain development demonstrated significantly weaker low‐frequency (delta, theta, alpha frequency band) connectivity. Neonates with brain injury also displayed delayed functional maturation of EEG background activity, characterized by greater background discontinuity. Interpretation: These data provide new evidence that early structural and microstructural developmental brain abnormalities can have immediate functional consequences that manifest as characteristic alterations of neuronal network connectivity. Such early perturbations of developing neuronal networks, if sustained, may be responsible for the persistent neurocognitive impairment prevalent in adolescent survivors of CHD. These foundational insights into the complex interplay between evolving brain structure and function may have relevance for a wide spectrum of neurological disorders manifesting early developmental brain injury.